2015
DOI: 10.4103/0973-6247.150939
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate analysis to assess the effect of packed red cell transfusion and the unit age of transfused red cells on postoperative complications in patients undergoing cardiac surgeries

Abstract: Background:Transfusion of blood components and age of transfused packed red cells (PRCs) are independent risk factors for morbidity and mortality in cardiac surgeries.Materials and Methods:We retrospectively examined data of patients undergoing cardiac surgery at our institute from January 1, 2012 to September 30, 2012. Details of transfusion (autologous and allogenic), postoperative length of stay (PLOS), postoperative complications were recorded along with other relevant details. The analysis was done in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The controversy of single unit transfusion still exists. Makroo et al and Paone et al have recently published that there is no statistical difference between one unit and two units of PRBCs in relation with acute surgical complications (odds ratio: 1.12, 95% confidence interval) ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 97%
“…The controversy of single unit transfusion still exists. Makroo et al and Paone et al have recently published that there is no statistical difference between one unit and two units of PRBCs in relation with acute surgical complications (odds ratio: 1.12, 95% confidence interval) ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 97%
“…The results of the present study reveal that those receiving over two units of PC during the treatment and surgery had a significantly higher PCT level compared to those receiving smaller PC quantities. The results of several previous studies have demonstrated that the increased PC transfused during surgery is associated with postoperative complications and higher rates of mortality and morbidity after surgery [ 10 12 ]. Additionally, some studies have previously shown that the rise in the PCT level among patients undergoing CABG is associated with the increased consequent complications [ 5 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%